Professional facilitator: Development of training courses to enhance the facilitator technique for Thai community enterprises through online media - Tidarat Chuenchaikit; Krissana Kiddee; Thanin Ratanaolarn (My University, 2023)
This study aims to develop a training course to enhance the techniques of a facilitator for Thai community enterprises using online media. The author collected data from sixty participants from Thai community enterprises in two sub-districts using cluster random sampling. Three research instruments, namely, training courses, knowledge tests and skill assessment forms were used for data collection. The data was analysed using statistics such as mean (X), standard deviation (SD), t- test dependent and one-sample t-test. The ultimate contribution of this research is to enhance the economic stability of community enterprises for sustainability and self-reliance according to Thailand’s government strategic plans and national policy.
Keywords: Facilitator; Sample (material); Management and Marketing Education